Studies in agricultural credit - Reserve Bank of India (Bombay, 1970)
The publication contains the reports of three field studies: Study of Intensive Agricultural District Programme, Study of Medium-term Agricultural Credit and Study of Long-term Agricultural Credit.
Carried out under the direction of V. M. Jakhade, adviser.
oo 23/01/2019
Loans
Keywords: Agricultural credit; Agriculture; India